Comparative Transcriptome Profile Analysis of Longissimus dorsi Muscle Tissues From Two Goat Breeds With Different Meat Production Performance Using RNA-Seq - Shen, Jiyuan; Hao, Zhiyun; Wang, Jiqing; Hu, Jiang; Liu, Xiu; Li, Shaobin; Ke, Na; Song, Yize; Lu, Yujie; Hu, Liyan; Qiao, Lirong; Wu, Xinmiao; et al. (Frontiers in Genetics, 2021)
Carcass weight, meat quality and muscle components are important traits economically and they underpin most of the commercial return to goat producers. In this study, the longissimus dorsi muscle tissues were collected from five Liaoning cashmere goats and five Ziwuling black goats with phenotypic difference in carcass weight, some meat quality traits and muscle components, and then histological quantitative of collagen fibers and the transcriptome profiles in the longissimus dorsi muscle tissues were investigated using RNA-Seq. The percentage of total collagen fibers in the longissimus dorsi muscle tissues from Liaoning cashmere goats was higher than those from Ziwuling black goats, suggesting that these Liaoning cashmere goats had poorer meat tenderness. An average of 15,919 and 15,582 genes were found to be expressed in longissimus dorsi muscle tissues from Liaoning cashmere goats and Ziwuling black goats, respectively. Compared to Ziwuling black goats, the expression levels of 133 genes were up-regulated in Liaoning cashmere goats, while 78 genes were down-regulated. Gene ontogeny (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that the differentially expressed genes (DEGs) were significantly enriched in GO terms related to the muscle growth and development and the deposition of intramuscular fat and lipid metabolism, hippo signaling pathway and Jak-STAT signaling pathway. The results provide an improved understanding of the genetic mechanisms regulating meat production performance in goats.